2015
DOI: 10.5194/acp-15-8101-2015
|View full text |Cite
|
Sign up to set email alerts
|

Peroxynitric acid (HO<sub>2</sub>NO<sub>2</sub>) measurements during the UBWOS 2013 and 2014 studies using iodide ion chemical ionization mass spectrometry

Abstract: Abstract. In this paper laboratory work is documented establishing iodide ion chemical ionization mass spectrometry (I − CIMS) as a sensitive method for the unambiguous detection of peroxynitric acid (HO 2 NO 2 ; PNA). A dynamic calibration source for HO 2 NO 2 , HO 2 , and HONO was developed and calibrated using a novel total NO y cavity ring-down spectroscopy (CaRDS) detector. Photochemical sources of these species were used for the calibration and validation of the I − CIMS instrument for detection of HO 2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 61 publications
2
42
0
Order By: Relevance
“…It showed very large signals at the mass normally interpreted as HONO with a distinct, daytime maximum. As described in Veres et al (2015), HO 2 NO 2 mixing ratios were observed to reach an average daytime maximum of approximately 4 % of NO z . Unpublished laboratory results suggest that a large fraction of the HO 2 NO 2 is detected as HONO using the acid CIMS, resulting in a positive daytime bias in the 2013 measurements.…”
Section: No Y Partitioning and No X Oxidationmentioning
confidence: 97%
“…It showed very large signals at the mass normally interpreted as HONO with a distinct, daytime maximum. As described in Veres et al (2015), HO 2 NO 2 mixing ratios were observed to reach an average daytime maximum of approximately 4 % of NO z . Unpublished laboratory results suggest that a large fraction of the HO 2 NO 2 is detected as HONO using the acid CIMS, resulting in a positive daytime bias in the 2013 measurements.…”
Section: No Y Partitioning and No X Oxidationmentioning
confidence: 97%
“…Laser-induced fluorescence (LIF) is a sensitive technique for OH radical measurements and it is used for the indirect detection of HO 2 by its conversion into OH after reaction with NO. The concurrent conversion of some specific RO 2 radicals can contribute to the HO 2 signal (Fuchs et al, 2011;Whalley et al, 2013;Lew et al, 2018). This can be minimised by reducing the NO concentration added to the sampled air for the conversion of HO 2 to OH, but at the cost of a reduced sensitivity.…”
mentioning
confidence: 99%
“…Gas flows containing low and reproducible concentrations of PNA were generated dynamically in a similar fashion 180 to the method described by Veres et al (2015) by combining the output of a HO2 photochemical source with NO2.…”
Section: Photolysis Sourcementioning
confidence: 99%